Cultura tributaria y su relación con la informalidad de los comerciantes de ventas de prendas de vestir de Belén, 2022 - Rios Vasquez, Alvaro Jesus (2023)
The objective of this research was to determine the relationship between the tax culture and the informality of clothing sales merchants in Belén, 2022, the type of quantitative level research, non-experimental design, descriptive type was used. And correlational. The sample is made up of clothing merchants from Belén, the survey was conducted on a total of 150 people, the result was that with a Pearson correlation value equal to 0.946** and the sigma value (bilateral) which is 0.000, we conclude that there is a significant relationship between the tax culture and the informality of clothing sales merchants in Belén,2022. After analyzing the dimensions of the variables and according to the response of more tan 70%, we conclude that both the tax culture variable and the informality variable have a “low” level and require signficant improvements. The investigation concluded that there is a significant relationship between the tax culture and the informality of clothing sales merchants in Belén, 2022.